Communication Adaptation and Customer Loyalty in Platform-Based Ride-Hailing Services: Evidence from Greater Jakarta - Ferane Aristrivani Sofian; Cindy Valencia Rizan; Tri Mega Asri; Manish Mathur; Marginata Kurnia Putra (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study explores whether drivers’ communication skills are positively related to attitudinal customer loyalty, how communication is adaptively enacted within short, platform-evaluated encounters in the Greater Jakarta metropolitan region, and how these adaptive practices relate to loyalty outcomes. An explanatory sequential mixed-methods design was employed. The quantitative phase involved 385 active ride-hailing users and applied descriptive statistics and Spearman’s rank-order correlation. The qualitative stage consisted of semi-structured interviews with seven experienced drivers, which were analyzed thematically using Communication Accommodation Theory. The findings show a moderate and statistically significant positive correlation between perceived drivers’ communication skills and attitudinal customer loyalty (ρ = .412, p < .001). Interview data suggest that each ride functions as a micro-communication arena in which drivers continually recalibrate tone, conversational depth, and embodied conduct in response to passengers’ cues, algorithmic visibility, and rating asymmetry. Communicative adaptation unfolds through situational convergence (alignment), strategic divergence (privacy-sensitive silence), evaluative convergence under rating pressure, and multimodal accommodation. These patterned adjustments stabilize brief encounters and shape evaluative judgments. In algorithmically governed environments, communication emerges not merely as a soft skill but as a context-sensitive relational practice linking interactional competence to loyalty intention in low-switching-cost platform markets.